The circulatory system. - World Book, Inc. (Chicago : World Book, 2007)
"An introduction to the circulatory system of the human body--one of six volumes in a set titled WORLD BOOK'S HUMAN BODY WORKS. Includes illustrations, glossary, resource list, and index"--Provided by publisher.
Includes bibliographical references (p. 47) and index.
Keywords: Cardiovascular system -- Juvenile literature; Heart -- Juvenile literature